RUSSIAN LANGUAGE TEACHING METHODOLOGY: CURRENT APPROACHES AND BEST PRACTICES (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This research paper provides an overview of Russian language teaching methodology, focusing on current approaches and best practices. The paper explores the historical development of Russian language teaching methods, highlighting key shifts and influential theories. It then examines the contemporary approaches to teaching Russian as a foreign language, including communicative language teaching, task-based instruction, and content-based instruction. Additionally, the paper discusses effective instructional strategies, materials, and assessment techniques for teaching Russian. By synthesizing the existing literature and research, this paper aims to provide language instructors and curriculum developers with valuable insights into the field of Russian language teaching methodology.